Biochemical characterization of lactic acid bacteria (LAB) isolated from home-made fermented durian flesh, tempoyak / Noor Azlin Yasmin Nordin ... [et al.] - Nordin, Noor Azlin Yasmin; Suzila, Mirlia; Lazim, Nurunnuha; Mohamed, Emida; Camalxaman, Siti Nazrina; Haron, Norhisham; Rambely, Azlin Sham (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Tempoyak is a fermented condiment made from durian fruit (Durio zibethinus). Tempoyak is prepared by the separation of flesh durian pulp from seed and then the flesh durian pulp is left to ferment for 7 days at ordinary temperature. Enumeration of lactic acid bacteria (LAB) is done on MRS agar and isolated single colony is picked up to perform morphological, cultural and biochemical test. The isolated colony from tempoyak showed LAB properties that include the ability to grow in MRS agar, Gram positive bacteria as well as negative for catalase test. Out of 10 from 28 bacteria that were isolated from tempoyak were categorized as LAB base on their morphological, cultural and biochemical characteristics. Identification of LAB is confirmed by using API 50 CHL strips kit. The results of API 50 CHL revealed 3 out of 10 are Lactobacillus plantarum and it is the predominant species in tempoyak. The other species that have been recognized were Lactobacillus brevis, Lactobacillus pentosus, Lactobacillus fermentum, Lactobacillus lactis, Lactobacillus raffinolactis, Lactobacillus casei, and Leuconostoc mesenteroides. Meanwhile, the LAB count varied in the range between 5.3 × 1010 to 1.24 × 1012 cfu/ml.